2005
DOI: 10.1111/j.1572-0241.2005.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Race and Ethnicity on Inflammatory Bowel Disease

Abstract: There are significant differences in IBD subtypes and serologic markers among racial/ ethnic groups with IBD in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
120
3
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(137 citation statements)
references
References 24 publications
13
120
3
1
Order By: Relevance
“…Previous studies indicated substantial racial/ethnic differences in the characteristics of IBD in the United States and worldwide [1,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]. Little data exists with regard to the prevalence of IBD in Blacks in the United States and in Asians outside Asia [23].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated substantial racial/ethnic differences in the characteristics of IBD in the United States and worldwide [1,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]. Little data exists with regard to the prevalence of IBD in Blacks in the United States and in Asians outside Asia [23].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, recently reported data have supported the supposition that IBD is no longer a rarity in non-Caucasians, although still less common than in the Caucasian population [1,2]. Also, inflammatory bowel disease may be increasing in incidence in certain US minority populations, including AfricanAmericans, according to hospital statistics [3][4][5].…”
mentioning
confidence: 83%
“…Several distinct genetic and environmental factors contribute to the pathogenesis of IBD, which is probably modulated by their complex interaction (8,9). Initial evidence for a genetic predisposition to the development of IBD stems from the observation of differences in the incidence of IBD between different ethnic groups (10). There is welldocumented evidence that Caucasians in Europe and North America have the highest rates of IBD, followed by Afro-Americans and then Asians (11).…”
Section: Chronic Inflammatory Bowel Diseases (Ibd) Includingmentioning
confidence: 99%